PRESEPSI STAKEHOLDER TERHADAP ELEMEN JALUR PEJALAN KAKI DI KAWASAN TAMAN GAJAH, KOTA BANDAR LAMPUNG - Saraswati, Zenia F; Alvianti, Vivian (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2022)
Taman Gajah area was developed into a Green Open Space and public space to accommodate the needs of the community. The transportation infrastructure, especially pedestrian, becomes the most important aspects in this development. This study aims to identify the perceptions of various stakeholders on the development of urban infrastructure based on their walking experience on pedestrian path. It is found that the stakeholders put pleasure elements in the form of the availability of pedestrian paths, the availability and placement of complementary facilities (street furniture), and the addition of ramps becomes the priority aspects in the development of pedestrian paths in Taman Gajah area.